2009
DOI: 10.1002/etc.87
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin‐LR modulates selected immune parameters and induces necrosis/apoptosis of carp leucocytes

Abstract: Microcystins (MCs) are potent hepatotoxins acting by the inhibition of protein phosphatase 1 and 2A, and may promote liver tumors. Moreover, studies also suggest they are nephrotoxic. The aim of the present study was to assess possible in vitro effects of microcystin-LR (which contains the amino acids leucine and arginine, the most widely studied and distributed variant of all microcystins) on the selected immune functions of the cells isolated from the head kidney of carp. In the experiments, pure microcystin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
(42 reference statements)
2
17
0
Order By: Relevance
“…4). Comparing the results of the present study with the results of previous studies, we can conclude that the lymphocyte proliferation and phagocytosis in cells incubated with the toxin mixture were more significantly decreased than those in MC-LR or ATX-a treatment alone [10,11,13,15]. The results suggest the synergistic effect of these various types of cyanotoxins.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…4). Comparing the results of the present study with the results of previous studies, we can conclude that the lymphocyte proliferation and phagocytosis in cells incubated with the toxin mixture were more significantly decreased than those in MC-LR or ATX-a treatment alone [10,11,13,15]. The results suggest the synergistic effect of these various types of cyanotoxins.…”
Section: Discussionsupporting
confidence: 76%
“…Rogers et al [16] concluded that the synergistic effect of MC-LR and ATX-a was due to the different routes toxin uptake. The results of our previous in vitro and in vivo investigations also showed that the extract containing MCs or ATX-a Anna Rymuszka et al induced greater suppressive effects on essential functions of immune cells (ROS production, lymphocyte proliferation and cytokine production) than the pure toxins alone [10][11][12][13]15]. Probably, the extract contained other unknown toxic metabolites produced by cyanobacteria which were responsible for the observed toxicity [17].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, we regarded this dualistic response to different doses of MCs as hormesis, which is a biphasic dose-response phenomenon and characterized by low-dose stimulation and highdose inhibition (Calabrese, 2008). Hormesis of MCs has also been reported in common carp pronephros phagocytes (Rymuszka et al, 2010), crucian carp , human amniotic epithelial (FL) cells (Liang et al, 2011), HeLa cells (Chen et al, 2014), and even plants, rape and cabbage (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the levels of expression of selected proinflammatory (IL-1 b, TNF-a) and anti-inflammatory (IL-10, TGFb) cytokines released from carp leukocytes, can largely help to explain changes in the functioning of phagocytes and lymphocytes observed in our previous studies [14,21], in response to in vitro exposure to selected cyanotoxins: MC-LR and Antx-a.…”
Section: Introductionmentioning
confidence: 99%